Kedudukan Hak Wanita Menurut Hukum Islam dan Hukum Perdata (KUHPerdata) - Kun Budianto (Universitas Islam Negeri Raden Fatah Palembang, 2019)
Islam specify womankind of dimiciling competent in elementary three things, that is: First, That Islam confess womankind existence fully and intact as also to man clan. Second, Islam give facility of womankind to claim Science and give to domicile which terhormaat in social field at various his life storey;level, start from final childhood until his soul. is Third, Islam pass to estae owner rights womankind perfectly in all matter its use, since they step on adult age and do not a even also allowed to meddle forcibly, that goodness by his husband and also by others. While Dimiciling woman in Civil Law among other things is: Woman assumed [by] [is] equal to men in obtaining rights, woman own freedom in obtaining its rights without there his boundary, except woman married and underage.